Gerakan Muhammadiyah dalam Membumikan Wacana Multikulturalisme: Sebuah Landasan Normatif-Institusional - Syamsuddin, Muh (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2017)
This paper examines the debate and internal dynamics of the Muhammadiyah’s da’wa movement in Kotagede on easing the multiculturalism context. With the debate, how did the Muhammadiyah of Kotagede understand the phenomenon of multiculturalism as the real life ultimate? So, how is the involvement of Muhammadiyah member institutionally in its role in addressing multiculturalism? Furthermore, what methods and strategies are applied in easing the discourse of multiculturalism? Departing from Nakamura’s early work, which examines the reformist-modernist movement in anthropological perspective, this article is also based on a phenomenological-naturalistic qualitative approach that reveals the truth of the facts in the field until it is interpreted to be a novelty of meaning. It’s expected can contribute positively to the development of multiculturalism in the framework of pluralism (diversity) and Pancasila to meet a harmonious nation life. Thus, the facts in the field found that the debate of Muhammadiyah member questioning the discourse of multiculturalism was preceded by the congress Bali in 2002s when the advisory of council (Dewan Tanwir) decided the meaning of amar ma’ruf nahi munkar (calling for good, preventing evil) was not only interpreted as textuality, but how the progressive movement that carried the issue of ‘cultural da’wa’ (dakwah kultural) was implemented well. Based on the result of a decision, Muhammadiyah’s own member internally can be mapped into three groups, namely puritan, moderate, and reformist. Although the ‘cultural da’wa’ is much opposed by the Puritans, in fact is just few agree with the group. The echoes of moderate and reformist groups are larger, the whole multicultural movement can be implemented well to the grassroots.Tulisan ini mengkaji tentang perdebatan dan dinamika internal gerakan dakwah Muhammadiya di Kotagede dalam membumikan konteks multikulturalisme. Dengan adanya perdebatan tersebut, bagaimana warga Muhammadiyah Kotagede memahami fenomena multikulturalisme sebagai realitas kehidupan hakiki? Lantas, bagaimana keterlibatan warga Muhammadiyah tersebut secara institusional dalam peranannya menyikapi multikulturalisme? Selanjutnya, metode dan strategi apa yang diterapkan dalam membumikan wacana multikulturalisme? Berangkat dari tesis awal Nakamura, yang mengkaji gerakan reformis-modernis dalam perspektif antropolog, artikel ini juga dilandasi dengan pendekatan kualitatif fenomenologis-naturalistis yang mengungkap kebenaran fakta di lapangan hingga diinterpretasikan menjadi sebuah kebaruan makna. Di mana harapannya dapat memberikan kontribusi positif bagi perkembangan multikulturalisme dalam bingkai pluralisme (diversity) dan pancasila guna menyongsong kehidupan berbangsa yang harmonis. Dengan begitu, fakta di lapangan ditemukan bahwa perdebatan warga Muhammadiyah menyoal wacana multikulturalisme diawali hasil muktamar Denpasar Bali tahun 2002 ketika dewan tanwir memutuskan makna amar ma’ruf nahi munkar tidak hanya dimaknai sebatas tekstualitas, tapi bagaimana gerakan berkemajuan yang mengusung isu ‘dakwah kultural’ diimplementasikan dengan baik. Dalam perjalanannya, hasil keputusan tersebut warga Muhammadiyah sendiri secara internal dapat dipetakan menjadi tiga kelompok, yakni puritan, moderat, dan reformis. Walaupun ‘dakwah kultural’ banyak ditentang oleh kelompok puritan, faktanya sedikit yang sepakat dengan kelompok tersebut. Gaung kelompok moderat dan reformis lebih besar, secara utuh gerakan multikulturalisme dapat diimplementasikan dengan baik hingga ke akar rumput (grassroots).